Analysis of Tool Wear and Hole Delamination for Large-Diameter Drilling of CFRP Aircraft Fuselage Components: Identifying Performance Improvement Drivers and Optimization Opportunities - Juan Fernández-Pérez; Carlos Domínguez-Monferrer; María Henar Miguélez; José Luis Cantero (Journal of Manufacturing and Materials Processing, 2023)
This study provides a comprehensive analysis of the one-shot drilling (CFRP) strategy for machining CFRP materials in the assembly of aircraft components, focusing on key factors such as tool wear, hole delamination, and the evolution of machining forces. The research uses adapted parts of the tail-cone structure of a commercial aircraft as workpieces and employs large-diameter cutting tools to perform drilling operations, with results that can be readily applied to the industry. The study selects cutting conditions by analyzing the effect of cutting parameters on tool life in drilled holes and accumulated cutting time, with the end-of-life criterion based on the extension of the wear suffered by the main cutting edge of the first step. The results show that all tested cutting conditions achieve a similar value of tool life expressed in terms of holes drilled, with differences smaller than 7%. However, one of the cutting conditions analyzed completes the same number of holes within 40% less time. Therefore, considering productivity criteria, it will be interesting to evaluate the use of high values for the cutting parameters. Overall, this research provides valuable insights for improving the efficiency and effectiveness of CFRP machining in aircraft manufacturing.